2020
DOI: 10.1007/s11606-020-05730-4
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Awareness and Common Misconceptions About Palliative Care Among Adults: Insights from a National Survey

Abstract: BACKGROUND: Despite recent growth in palliative care programs palliative care remains underutilized. Studies suggest that patients and providers commonly associate palliative care with end of life, often leading to misconceptions and late referrals. OBJECTIVE: To characterize self-reported palliative care knowledge and misconceptions about palliative care among US adults and demographic, health, and social r o l e f a c t o r s a s s o c i a t e d w i t h k n o w l e d g e a n d misconceptions.DESIGN: We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 14 publications
3
44
0
Order By: Relevance
“…Similar to research with the general population in another context such as the USA [ 28 , 29 ], this study shows that knowledge about PC in Ecuador is generally low, which may lead to under-utilization and missed opportunities to improve the quality of care for people who may benefit from it. The results also highlight some specific areas where people show more misconceptions, for example, explicitly differentiate PC from pain management, that PC can be given together with curative treatments and from the onset of the disease, that it can be provided by personnel with basic PC training (depending on the level of complexity), and that PC is are not provided only in specialized health institutions.…”
Section: Discussionsupporting
confidence: 71%
“…Similar to research with the general population in another context such as the USA [ 28 , 29 ], this study shows that knowledge about PC in Ecuador is generally low, which may lead to under-utilization and missed opportunities to improve the quality of care for people who may benefit from it. The results also highlight some specific areas where people show more misconceptions, for example, explicitly differentiate PC from pain management, that PC can be given together with curative treatments and from the onset of the disease, that it can be provided by personnel with basic PC training (depending on the level of complexity), and that PC is are not provided only in specialized health institutions.…”
Section: Discussionsupporting
confidence: 71%
“…Our data echoes the 2018 Health Information National Trends Survey (Cycle 2) that shows 74% of non-Hispanic Black adults in the United States report not knowing about palliative care, and those who have some knowledge of palliative care are most likely to confuse it with hospice care. 14 Indeed, our data revealed that compared to hospice care and advance directives, palliative care was the most unknown type of care among both Hispanics and non-Hispanic Blacks, indicating that 3 out of 4 never heard about palliative care. We also documented significant racial gaps regarding awareness of hospice care, indicating that 5%, 18%, and 34% of non-Hispanic Whites, Hispanics, and non-Hispanic Black participants, respectively, reported lack of awareness of hospice care.…”
Section: Discussionmentioning
confidence: 76%
“…57 The 2018 Health Information National Trends Survey (Cycle 2) shows that 3 out of 4 (74%) non-Hispanic Black adults in the United States report not knowing about palliative care, and those who have some knowledge of palliative care are most likely to confuse it with hospice care. 17 In addition, it has been documented that uninsured and minority patients are less likely to receive hospice care and are more likely to have a delay in transition to hospice care when compared to their insured Caucasian counterparts. 106 While a few researchers suggest that disparity in use of hospice care is due to patient preference, others suggest physician bias as a factor.…”
Section: Methodsmentioning
confidence: 99%
“…After searching almost fourthly-thousand citations, 284 articles were included in our study, of which 147 were manuscripts that directly addressed end-of-life and hospice care, palliative care, as well as advance care planning and directives that include non-Hispanic Blacks. 4 …”
Section: Methodsmentioning
confidence: 99%